Slope Reinforcement using X Type Block in Precipitation - Ignatius Evan Yesa; Tri Harianto; Ariningsih Suprapti (International Association of Lowland Technology, 2022)
This study was applied research by using experimental method to determine the effectiveness of slope type reinforcement block X on slopes with rainfall (precipitation). The output data of was the amount of deformation on the slopes and the ratio of the deformation of slope reinforcement. Based on the results of the study, the slopes loaded without reinforced with block X with the provision of rainfall experienced a collapse in 28 minutes. The deformations occurred just before the failure occurred were vertical deformation of 8 mm and horizontal deformation of 10 mm. Afterwards, the slopes with block X type 1 reinforcement after being loaded for 24 hours, has remained no collapse. The deformations occurred are (1) vertical deformation of 8 mm and (2) 10 mm of horizontal deformation